Long-Term Stability of Pr2NiO4+δ Air Electrodes for Solid Oxide Cells against Chromium Poisoning. Issue 1 (27th January 2021) - Schrödl, Nina; Egger, Andreas; Lammer, Judith; Hofer, Ferdinand; Sitte, Werner
Abstract : Long-term stability tests are performed at 800 °C on Pr2 NiO4+ δ air electrodes by use of a symmetrical button cell with Ce0.9 Gd0.1 O1.95 as solid electrolyte. The experiments are carried out by means of electrochemical impedance spectroscopy and current-voltage measurements with and without current load under dry and humid conditions in the presence of a chromium source. Chromium poisoning of Pr2 NiO4+ δ air electrodes is investigated for periods of several hundred hours at 30% relative humidity. In order to separate the influence of anodic and cathodic electrode polarization on Cr-deposition, measurements are conducted using a Pt-reference electrode. The electrode performance is found to remain fairly stable under dry conditions, even when a current is drawn. However, after volatile Cr-species in a humid atmosphere are introduced, the cell performance starts to deteriorate and the polarization resistance contribution of the SOFC cathode increases significantly. After several thousand hours, the electrodes are analyzed by means of analytical electron microscopy. Detailed post-test analyses provide evidence for a correlation between the extent of Cr-deposition and electrode degradation in SOFC as well as SOEC mode. Based on these findings, enhanced resilience of Pr2 NiO4+ δ against Cr-poisoning in SOEC mode can be established.